Das Kosmopolitische als „erscheinende Welt“ – über Pluralität und Weltbürgerlichkeit als Parameter der Weltoffenheit bei Hannah Arendt - Kurbacher, Frauke A. (HannahArendt.net, 2023)
The cosmopolitan is constitutivley related to a concept of the world that needs to be considered.While Hannah Arendt’s understanding of the world, based on the Vita activa, is understood primarily for good reasons as one in the relationship between persons and thus as political in a broad anthropological sense, however, she reflects the world in her late work on the basis of the philosophical concept of appearance and gives it its own imprint within her ‘phenomenology of appearance’, which connects it with thoughts on cosmopolitanism with which she in turn draws on Kant. With recourse to philosophical appearance and Kant’s cosmopolitanism, the understanding of the world now reaches far beyond the interpersonal and at the same time shows human responsibility for all possible world contexts. Both approaches, both of Arendt’s and Kant’s, are positioned in recourse to appearance for environmental philosophical approaches as well as for current climate-theoretical connections, without the cosmopolitanism associated with the conception of worldliness and openness to the world being absorbed in this alone.